Paleobotanical evidence for Mediterranean climates in the western Canadian Paleoarctic during the late middle Eocene - West, Christopher K.; Reichgelt, Tammo; Reyes, Alberto V.; Buryak, Serhiy D.; Staniszewska, Kasia J.; Basinger, James F. (My University, 2024)
Paleogene age deposits east of the Fifteenmile River, northwest of Dawson City, Yukon, Canada preserve a diverse high-latitude fossil flora. Here, we provide new data on the age of the fossil site based on laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) U-Pb dating of tephra zircons, paleobotanical paleoclimate reconstructions, and growing season length estimates based on photoperiod. These new data indicate an age of the Fifteenmile River fossil locality as late middle Eocene and likely within the Middle Eocene Climatic Optimum episode. The paleoflora-based paleoclimate reconstruction indicates the region was relatively wet and warm with non-freezing winters, but also experienced seasonal dryness, with an approximate 7 months long growing season as suggested by photoperiod. We interpret this paleoclimate as summer dry and winter wet—a climate analogous to modern day warm Mediterranean climates in the Köppen-Geiger climate classification system. These findings provide a new perspective on the past climate and environment of high-latitude ecosystems during warm greenhouse intervals and contribute to our understanding of the Earth's climate history and its potential future changes.
Keywords: Paleogene age deposits; late middle Eocene; Middle Eocene Climatic Optimum episode; western Canadian Paleoarctic